2005
DOI: 10.1111/j.1945-5100.2005.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Impactites of the Haughton impact structure, Devon Island, Canadian High Arctic

Abstract: Abstract-Contrary to the previous interpretation of a single allochthonous impactite lithology, combined field, optical, and analytical scanning electron microscopy (SEM) studies have revealed the presence of a series of impactites at the Haughton impact structure. In the crater interior, there is a consistent upward sequence from parautochthonous target rocks overlain by parautochthonous lithic (monomict) breccias, through allochthonous lithic (polymict) breccia, into pale grey allochthonous impact melt brecc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
123
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(136 citation statements)
references
References 49 publications
(76 reference statements)
12
123
1
Order By: Relevance
“…It follows that clasts within "cooler" impact ejecta and central uplift lithologies are likely to remain vesicular; whereas, clasts enclosed in hot, impact-melt bodies in the crater interior will likely recrystallize. At Haughton, the sediment-derived impact-melt breccias cooled very quickly so that many of these vesicular habitats were preserved (Osinski et al 2005b), however, impact-melt layers generated from crystalline-rich targets remain at much higher temperatures for extended lengths of time (e.g., Grieve et al 1977) so that the thermal annealing and recrystallization of vesicular clasts will be more likely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It follows that clasts within "cooler" impact ejecta and central uplift lithologies are likely to remain vesicular; whereas, clasts enclosed in hot, impact-melt bodies in the crater interior will likely recrystallize. At Haughton, the sediment-derived impact-melt breccias cooled very quickly so that many of these vesicular habitats were preserved (Osinski et al 2005b), however, impact-melt layers generated from crystalline-rich targets remain at much higher temperatures for extended lengths of time (e.g., Grieve et al 1977) so that the thermal annealing and recrystallization of vesicular clasts will be more likely.…”
Section: Discussionmentioning
confidence: 99%
“…This unit has a maximum preserved thickness of ~125 m and covers an area ~60 km 2 (Scott and Hajnal 1988). The original dimensions of the impact-melt breccia deposit are estimated to be greater than 200 m in thickness and ~12 km in diameter (Osinski et al 2005b). In the eastern part of the crater, the impact-melt breccia deposits are divided into a series of discrete outcrops separated from the main deposits in the central part of the crater by a system of broad (up to ~1 km wide) alluvial terraces associated with meanders of the Haughton River.…”
Section: Characteristics Of the Field Sitementioning
confidence: 99%
See 1 more Smart Citation
“…However, Ozinski et al (2005) found that CaCO 3 melts in the Haughton impact crater coexist with silicate melt. In addition, intact, well-preserved carbonate microfossils are found encased in silicate melt from Chicxulub (Salge, 2007).…”
Section: Comments and Repliesmentioning
confidence: 99%
“…A paper by Osinski et al (2005b) builds upon previous works by Spray (2001, 2003) and improves our knowledge of the response of sedimentary rocks, in particular carbonates, to a hypervelocity impact. In particular, it is now clear that carbonates, evaporites, sandstones, and shales, underwent melting during the Haughton impact event, a fact that was not recognized prior to HMP studies.…”
mentioning
confidence: 99%